PPAT's Obligation in Providing Free Services to Indigent People - Ilham Ilham; Sudirman Sudirman; Wahyudi Umar; Ismi Fadjriah Hamzah (JURNAL AKTA, 2024)
PPAT Temporarily must provide free services to people who are unable to obtain an Authentic Deed of land rights or property rights to flats, which is strong evidence in the legal process. However, existing regulations governing this matter can lead to multiple interpretations and incomplete documentation requirements, making it difficult for Land Deed Making Officials (PPAT) to fulfill their obligations. Therefore, the application of standardization by PPAT depends on the interpretation of each individual, because it is not regulated in applicable regulations. This study aims to analyze regulations, literature, and interviews with PPAT to find out how they fulfill their responsibilities. This research used normative legal research which reveals that misinterpretation is caused by two factors, namely the absence of criteria to determine a person's incompetence and the imprecise requirements to guarantee its accuracy. The conclusion show better provide services to the community, it is necessary to establish clear criteria and standards for individuals who are unable to carry out legal actions in the field of land and flats.